Rapid, High-Resolution, Label-Free, and 3-Dimensional Imaging to Differentiate Colorectal Adenomas and Non-Neoplastic Polyps With Micro-Optical Coherence Tomography. Issue 6 (June 2019) - Ding, Qianshan; Deng, Yunchao; Yu, Xiaojun; Yuan, Jingping; Zeng, Zhi; Mu, Ganggang; Wan, Xinyue; Zhang, Jun; Zhou, Wei; Huang, Li; Yao, Liwen; Gong, Dexin; et al.
Abstract : INTRODUCTION: "Resect and discard" paradigm is one of the main strategies to deal with colorectal diminutive polyps after optical diagnosis. However, there are risks that unrecognized potentially malignant lesions are discarded without accurate diagnosis. The purpose of this study is to validate the potential of micro-optical coherence tomography (μOCT) to improve the diagnostic accuracy of colorectal lesions and help endoscopists make better clinical decision without additional pathology costs. METHODS: Fresh tissue samples were obtained from patients with colorectal polyps or colorectal cancer who received endoscopic therapy or laparoscopic surgery. These samples were instantly imaged by μOCT and then sent to pathological evaluation. Then, μOCT images were compared with corresponding HE sections. We created consensus μOCT image criteria and then tested to determine sensitivity, specificity, and accuracy of our system to discriminate neoplastic polyps from non-neoplastic polyps. RESULTS: Our μOCT system achieved a resolution of 2.0 μm in both axial and lateral directions, clearly illustrated both cross-sectional and en face subcellular-level microstructures of colorectal lesions ex vivo, demonstrating distinctive patterns for inflammatory granulation tissue, hyperplastic polyp, adenoma, and cancerous tissue. For the 58 cases of polyps, the accuracy of the model was 94.83% (95% confidence interval [CI], 85.30%–98.79%), the sensitivity for identification of adenomas was 96.88% (95% CI, 82.89%–99.99%), and the specificity was 92.31% (95% CI, 74.74%–98.98%). Our diagnostic criteria could help both expert endoscopists and nonexpert endoscopists to identify neoplastic from non-neoplastic polyps with satisfactory accuracy and good interobserver agreement. DISCUSSION: We propose a new strategy using μOCT to differentiate benign polyps and adenomas after the lesions are resected. The application of μOCT can potentially reduce the cost of pathological examination and minimize the risk of discarding malignant lesions during colonosocpy examination.